Analisis Pengaruh Potongan Harga, Paket Bonus, Pajangan dalam Toko dan Suasana Toko Terhadap Perilaku Pembelian Impulsif Pada Pelanggan Minimarket Indomaret Hybrid di Kota Semarang - Aria Ahmad Pradana; Retno Yustini Wahyuningdyah (JEMAP, 2019)
The purpose of this research is to analyze the effect of discount, bonus pack, in-store display, and store atmosphere towards customer’s impulsive buying decision. The amount of sample in this research is 120. Sampling technique used in this research is purposive sampling and analyzed by multiple linear regression analysis using SPSS version 19. The result showed that discount has a significant and positive effect towards impulsive buying decision; bonus pack has a significant and positive effect towards impulsive buying decision; in-store display has a significant and positive effect towards impulsive buying decision; and store atmosphere has a significant positive effect towards impulsive buying decision.